The Influence of Interval Training Method on The 60 Meters Running in Primary School Students. - Setiawan, Tri Alfian; Indah Permatasari, Vigi; Ahmadi, Dedi (INSPIREE: Indonesian Sport Innovation Review, 2023)
The  purpose  of  the study. This research is motivated by the results of the 60 meter run conducted by the fifth grade students of primary school negeri 009 Simpang Kubu, Kampar Regency, which is not optimal and not appropriate in its implementation. Materials and methods. Research Methods This research uses a pre-experimental method with One Group, namely Pre-test and Post-test Design. The data collection technique was simple random sampling with inclusion and exclusion criteria. Data analysis in this study used the Wilcoxon test, Paired Sample T-test. Results. Data analysis in this study used the Wilcoxon test, Paired Sample T-test. The results of the study based on the statistical output of "Test Statistics", it is known that Asymp.Sig (2-tailed) is worth 0.000. Because the value of 0.000 is less than 0.05. It can be concluded that "there is a significant difference between pre-test scores and post-test scores. Conclusions. The conclusion in this study is that there is a significant effect between this interval exercise and the results of a 60 meters run on fifth grade students of primary school Negeri 009, Kampar Regency.